Immunoanalysis indicates that the sodium iodide symporter is not overexpressed in intracellular compartments in thyroid and breast cancers (2009)
Objective: The active transport of iodide into thyroid cells is mediated by the NaC/IK symporter (NIS) located in the basolateral membrane. Strong intracellular staining with anti-NIS antibodies has been reported in thyroid and breast cancers. Our initial objective was to screen tumour samples for intracellular NIS staining and then to study the mechanisms underlying the altered subcellular localization of the transporters. Methods: Immunostaining using three different anti-NIS antibodies was performed on paraffinembedded tissue sections from 93 thyroid or breast cancers. Western blot experiments were carried out to determine the amount of NIS protein in 20 samples. Results: Using three different anti-NIS antibodies, we observed intracellular staining in a majority of thyroid tumour samples. Control immunohistochemistry and western blot experiments indicated that this intracellular staining was due to non-specific binding of the antibodies. In breast tumours, very weak intracellular staining was observed in some samples. Western blot experiments suggest that this labelling is also non-specific. Conclusions: Our results strongly indicate that the NIS protein level is low in thyroid and breast cancers and that the intracellular staining obtained with anti-NIS antibodies corresponds to a non-specific signal. Accordingly, to increase the efficiency of radiotherapy for thyroid cancers and to enable the use of radioiodine in the diagnosis and therapy of breast tumours, improving NIS targeting to the plasma membrane will not be sufficient. Instead, increasing the expression level of NIS should remain the major goal of this field.